Dividend Announcement and Informational efficiency: A Sector Specific Study on Indian Stock Markets - Sharma, Renuka (Gyan Management Journal, 2010)
economy, some key industrial segments may have more reliable potential of consistent performance than the other segments. So even being at the disposal of the same type of· -:ation related to different sectors, it can be conceived by the investors in a heterogeneous manner .
Keywords: AARs; CAARs; Dividend Announcements; Event Study; Informational efficiency